2007
DOI: 10.1177/000841740707400303
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Students' and Graduates' Satisfaction with Professional Education and Preparedness for Practice

Abstract: The results of this evaluation may have important implications for educational programs, students, graduates, fieldwork supervisors, and employers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
119
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(130 citation statements)
references
References 10 publications
6
119
2
3
Order By: Relevance
“…This has been most notably experienced within community mental health teams where consensus regarding the optimal type of casework for occupational therapists has not been reached 26,30 . Consequently graduates need to project a strong professional identity, demonstrate skills in evidence-based practice, critical thinking and resilience 31,32 . Further, the accepted understanding of the role of occupational therapy practice must be widened to encompass the diversity of what the profession has to offer 33 .…”
Section: Background Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…This has been most notably experienced within community mental health teams where consensus regarding the optimal type of casework for occupational therapists has not been reached 26,30 . Consequently graduates need to project a strong professional identity, demonstrate skills in evidence-based practice, critical thinking and resilience 31,32 . Further, the accepted understanding of the role of occupational therapy practice must be widened to encompass the diversity of what the profession has to offer 33 .…”
Section: Background Literaturementioning
confidence: 99%
“…Whilst there has been little focus on mental health occupational therapy practice preparation, a number of studies have taken a broader curriculum view 31,34,35,36,37,38,39 . Such studies, whilst addressing a range of practice and education themes, typically reveal that new graduates grapple with low confidence when entering the working world 31 . They have difficulty making the shift from student to graduate and the need for support structures to be put in place is evident 36 .…”
Section: Background Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Professional identity, in particular, has been found to affect overall job satisfaction which, in turn, impacts on the retention of therapists within the occupational therapy profession [10]. A study of seventy-four occupational therapists from the United Kingdom found that many new graduates place an emphasis on profession-specific supervision as a means of building their professional skills and identity [11].…”
Section: Introductionmentioning
confidence: 99%